New governance for rural America : creating intergovernmental partnerships - Radin, Beryl (Rural America (Lawrence, Kan.), 1996)
Throughout the 1990s public demand for a fundamental shift in the relationship between government and its citizens has intensified. In response, a "new governance" model has emerged, emphasizing decreased federal control in favor of intergovernmental collaboration and increased involvement of state, local, and private agencies. One of the best examples of new governance can be found in the National and State Rural Development Councils (NRDC and SRDC), created in 1990 as the result of President Bush's Rural Development Initiative and called the Rural Development Partnership in the Clinton administration. In this first detailed analysis of the NRDCs and SRDCs, the authors examine the successes and failures of the original eight councils in Kansas, Maine, Mississippi, Oregon, South Carolina, South Dakota, Texas, and Washington, as well as eight other councils subsequently created in Iowa, New Mexico, North Carolina, Vermont, New York, North Dakota, Utah, and Wyoming.